PENERAPAN PENGAMANAN OBJEK VITAL, PENGAMANAN MANAJEMEN FILE, DAN PENGAMANAN CYBER PADA RUMAH SAKIT - Fadilah Fitria Harahap; Edy Soesanto, Jelita Cahya Seruni, Onik Wahyu Utami (Jurnal Komunikasi, 2024)
A hospital is an organization that provides health services with various facilities, technology and trained human resources. In providing superior quality service. Hospitals need to ensure that their vital objects, file management and cyber are protected from security threats. Therefore, this research aims to find out how to implement vital object security, file management security, and cyber security in hospitals. The method used in this research uses literature study. Literature study is a method of collecting data by understanding and studying theories from various literature related to the research being made. Data analysis carried out in this research used content analysis. The research results in this paper state that vital hospital objects include: Buildings, infrastructure and medical equipment. The file management discussed is medical record management. And to maintain cyber security, you can implement an action plan if there is an attack/hacking, prepare investigation procedures and collect information from the attack/hacking including the type of attack that occurred (eg ransomware or information theft), diagnosis of affected equipment, analysis of vulnerable points. or vulnerable areas that provide opportunities for hacking) and have a contact list of relevant government agencies for further handling.